Dynamic manifestations of a conformal anomaly in engineered topological metals - Matthew J. Gilbert (Communications Physics)
Abstract The appearance of inconsistencies between classically conserved quantities and their quantum counterparts indicates the presence of an anomaly. While natural in high-energy physics, the appearance of anomalies in condensed matter is a subject of intense research reliant upon the complex bandstructures of topological metals. In this work, we present theoretical evidence supporting the presence of a conformal anomaly in conventional trivial spin-orbit coupled Josephson junctions. The conformal anomaly is underpinned by an emergent Weyl metal phase embedded in a non-trivial curved spacetime arising from the interplay between conventional quasiparticle bands and spatially-dependent superconducting order. We reveal that the conformal anomaly is unambiguously manifest as an enhanced Josephson current with a corresponding halving of the Josephson frequency at band critical points within the time-dependent non-linear response theory of open quantum systems. Furthermore, we illustrate that the anomalous response is broadly tunable using either electric field gating or applied magnetic fields. The presence of a conformal anomaly in a system as simple as a trivial Josephson junction portends a new pathway to study the merger of high-energy and condensed matter physics and, crucially, may force a reexamination of the physics hidden within combinations of individually ordinary materials.